Lectotypification of the name Fimbristylis cioniana (Cyperaceae) - D’antraccoli, Marco; Roma-Marzio, Francesco; Astuti, Giovanni; Maccioni, Simonetta; Peruzzi, Lorenzo (Phytotaxa, 2017)
The present contribution is part of an ongoing work promoted by the Italian Botanical Society aimed to recognize and typify all the taxa described from Italy and their loci classici, in order to increase their systematic knowledge and promote further studies (Domina et al. 2012, Peruzzi et al. 2015).